2020
DOI: 10.1080/00380768.2020.1851144
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical responses of mycorrhizal-inoculated Lamiaceae (Lavender, Rosemary and Thyme) plants to drought: a field study

Abstract: Mycorrhizal symbiosis may help plants to compensate the water deficit-induced macronutrients, secondary metabolites and osmotic adjustments as the basis of crop production. The present investigation was undertaken to evaluate the physiological responses of the lavender (Lavandula officinalis L.), rosemary (Rosmarinus officinalis L.) and thyme (Thymus vulgaris) host plants to inoculation with mycorrhizal fungi (Funnelliformis mosseae, Rhizophagus irregularis compared with non-inoculated control treatment) in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
1
13
1
Order By: Relevance
“…The aforementioned results are in conformity with those reported by Mohammadzadeh and Pirzad (2020) on (Lavandula officinalis L.), rosemary (Rosmarinus officinalis L.) and thyme (Thymus vulgaris L.).…”
Section: Total Carbohydrates (%)supporting
confidence: 92%
“…The aforementioned results are in conformity with those reported by Mohammadzadeh and Pirzad (2020) on (Lavandula officinalis L.), rosemary (Rosmarinus officinalis L.) and thyme (Thymus vulgaris L.).…”
Section: Total Carbohydrates (%)supporting
confidence: 92%
“…The average SPAD values of the treatments are shown in Table 3. In another experiment on garden thyme, it was found that water deficiency had a negative effect on the chlorophyll content of the leaves (Mohammadzadeh, Pirzad, 2020); however, it has not been manifested obviously in our experiment. Nevertheless, some authors have found opposite reactions, as the chlorophyll content increases with the increased drought stress in garden thyme (Ashrafi et al, 2018); however, in basil, the chlorophyll content decreased with the reduced soil water content (Damalas, 2019).…”
Section: Resultscontrasting
confidence: 78%
“…Similarly, Zhang et al (2019a) also concluded that AMF inoculation in field led to 16% increase on cereal yield, which is the same tendency to our study. Numerous studies have confirmed that the dependency of host plant on AMF was higher in stress environments than in no-stress environments ( Latef et al, 2016 ; Hu et al, 2017 ; Mohammadzadeh & Pirzad, 2021 ). Furthermore, There are differences between grain crops and non-grain crops by AMF, which probably because the positive effect of AMF on yield depends on the plant species ( Tarraf et al, 2015 ).…”
Section: Discussionmentioning
confidence: 98%